Management of human resources in family administration companies (Research, Society and Development, 2022)
Family businesses are an important part of the Portuguese economic fabric. Research has been conducted under various investigative prisms, mainly through Education. This type of company, which is owned by the family, is associated with a specific management matrix. The analysis performed focused on comparing non-family business models and three definitions of family property management. The field of study of people management, in this specific type of companies, has made progress in recent years, although still very small. The present work aims to analyze the possibility of generational influence in the definition of human resources management policies in the context of family businesses. The research was based on the literature on family business management, life, its comparison with non-family businesses, differences between family, ownership and management and professional management of family businesses. A study will be presented to identify and classify the family, a group of companies target of analysis and their human resources management practices, will allow to highlight the existence of different thoughts between the two generations of the family (first and second) with management functions, how resource management should be seen and defined people. The conclusions of the study will contribute to a better clarification of the causal relationship between human resource management practices and the strategic options adopted in this area by the interviewees, to see (possible) the difference is determined by the generation to which they belong.